DETERMINAN HARGA, KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MEREK MAKE OVER PADA MASYARAKAT CENGKARENG - Budiman Abdulah; Dewa Putu Yohanes Agata L. Sandopart; Nurjanah Nurjanah (Yayasan Education and Social Center, 2023)
This study aims to find out empirical evidence of the effect of price, service quality and promotion on purchasing decisions for make over cosmetic products in the Cengkareng community. The population in this study is the Cengkareng community who use cosmetic brand make over products. The research used google form and the type of research used in this study was quantitative and used the slovin formula to obtain a total sample of 100 people. The data analysis technique used is validity and reliability. Data were analyzed using classical assumption test techniques, multiple linear regression analysis, F test, t test, and coefficient of determination using SPSS 22 software. The results of this study indicate that the variables of price, service quality and promotion have a positive and significant effect on purchasing decisions for make over cosmetic products in the Cengkareng community, which means that the implications of the variables above indicate the level of purchasing decisions in the Cengkareng area community, indicating that price, service quality and promotion have a very important role. influence and give a positive view to the Cengkareng community in determining the purchase of cosmetic brands circulating in the market